Effects of placental cord drainage in the third stage of labour: A meta-analysis - Hang-lin Wu (Nature Portfolio, 2017)
Abstract Observational studies have demonstrated that placental cord drainage can shorten the length of the third stage of labour and reduce blood loss during vaginal deliveries. The aim of our work was to evaluate the existing evidence for the effectiveness of placental cord drainage in the third stage of labour. PubMed, Embase, the Cochrane Library, Web of Science, Google Scholar and 50 journals were searched up to the 4th of June, 2017. Randomized controlled trials comparing placental cord drainage with no cord drainage in the third stage of labour during vaginal delivery were included. Nine studies with 2653 participants were included. Compared with clamping the umbilical cord, umbilical cord drainage during the third stage of labour shortened the third-stage duration by 2.28 minutes (95% confidence interval (CI), −3.22 to −1.33), but did not reduce the amount of blood loss (−31.99 mL, −86.08 to 22.09). For women with normal vaginal deliveries, the incidence of postpartum haemorrhage was reduced by 3%. Placental cord drainage is a simple and non-invasive procedure that should be considered after delayed cord clamping. Further studies about the physiological processes and effects of placental cord drainage in additional circumstances are needed.